The Effect of Using the Trajist Model on the Levels of Mathematical Comprehension among First-Year Intermediate Students in Mathematics (Journal of the College of Basic Education, 2025)
The research aims to know the effect of using the Trajist model on the levels of mathematical understanding among first-year middle school students in mathematics. The researcher used the experimental design with partial control with two equivalent groups. The research sample was taken from the research community, which was represented by the government daytime middle and secondary schools affiliated with the General Directorate of Education in Baghdad/Karkh/3. The choice fell on Al-Weam Secondary School for Boys. The researcher identified the scientific material represented by chapters (five, six, and seven) of the mathematics book for the first-year middle school (6th edition, 2023). He prepared a test of mathematical understanding levels in mathematics consisting of (40) objective paragraphs of the (multiple-choice) type with four alternatives. After applying the research tool and analyzing the results of the research test statistically, the results showed that the students of the experimental group outperformed the students of the control group in the test of mathematical understanding levels. In light of the results, the researcher concluded the following: First: Using the Trajist model in teaching has a positive impact on the levels of mathematical understanding among first-year middle school students in mathematics compared to the traditional method. Second: Teaching according to the Trajist model makes students more active and energetic in class compared to teaching using the traditional method. According to the research results, the researcher recommends: First: Using the Trajist model in teaching mathematical concepts due to its positive impact on the levels of mathematical understanding. Second: Providing the necessary time for teaching according to modern strategies and models, as mathematics is a difficult and rigid subject that contains abstract concepts and mathematical problems, so it requires a long time for the information to reach the students' minds.